PENGARUH WORD OF MOUTH COMMUNICATION, BRAND TRUST, DAN SERVICE QUALITY TERHADAP KEPUTUSAN PENGGUNA PERAWATAN KECANTIKAN (Studi Kasus Pada Konsumen Perempuan di Larissa Aesthetic Center Semarang) - Eka Trinia Widiyanti; Wahyu Hidayat; Sari Listyorini (Universitas Diponegoro, 2015)
Nowadays, many emerging beauty clinics that offer a wide variety of beauty care services and products to meet the needs of care, especially for women. There are several factors that influence the choice of consumers to buy a product, among others, the word of mouth communication, brand trust, and service quality. The purpose of this research was to determine the influence of word of mouth communication, brand trust, and service quality on user’s decision of beauty treatments in Larissa Aesthetic Center Semarang. This type of research is explanatory research. The population in this research is consumers of Larissa Aesthetic Center Semarang and the number of samples taken was 100 respondents. The sampling technique used in this research is purposive sampling. The technique of collecting data using questionnaires, interview, and a study of literature. The analytical method used is the correlation test, determination, cross tabulations, simple linear regression, multiple, t test and F test with SPSS. The results of this research show that based on the results of multiple linear regression, word of mouth communication, brand trust, and service quality has positive influence on user’s decision of beauty treatments.